Preparation method of ultrathin copper foil and method for preparing copper-clad plate by using ultrathin copper foil

Ultrathin copper foil is prepared by a combination process of a non-metal peelable carrier substrate and a modified liquid, and antioxidant treatment is carried out under a vacuum antioxidant atmosphere, which solves the problem of high production cost and easy oxidation of ultrathin copper foil, and realizes the problem of high production cost and easy oxidation of ultrathin copper foil. Stable and environmentally friendly copper clad plate preparation.

CN119145012APending Publication Date: 2024-12-17SUINING LIHE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308758.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing ultra-thin copper foil is high in production costs and is easy to oxidize, making it difficult to effectively prevent oxidation problems during the preparation process, affecting the advancement of packaging load plate technology.

Method used

The ultrathin copper foil is prepared by a non-metal peelable carrier substrate and a modified liquid. The ultrathin copper foil is prepared by a combination of organic active layer and electroplating copper solution, and antioxidant treatment is carried out under a vacuum antioxidant atmosphere. Copper clad plate is prepared by hot pressing technology.

Benefits of technology

It reduces the overall cost of ultra-thin copper foil, prevents oxidation problems, ensures the stability of copper foil in storage and transportation, and achieves a good combination with semi-cured sheets to meet environmental protection needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145012A_ABST
    Figure CN119145012A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an ultrathin copper foil and a method for preparing a copper-clad plate by using the ultrathin copper foil. The method comprises the following steps: step 01, soaking a carrier substrate in a degreasing agent to remove oil stains on the surface; the method comprises the following steps: step 02, preparing an organic active layer on the surface of a cleaned carrier substrate, the thickness of the organic active layer being 1500-5000, step 03, immersing the carrier substrate treated in the step 02 into a modification liquid B, step 04, placing the carrier substrate treated in the step 03 into an electroplating copper liquid to prepare an ultrathin copper foil through electro-deposition, and step 05, carrying out electro-deposition on the ultrathin copper foil to prepare the ultrathin copper foil. The ultrathin copper foil obtained after treatment in the step 04 is subjected to washing and drying treatment; and step 06, performing antioxidant treatment on the surface of the ultrathin copper foil prepared in the step 05 in a vacuum antioxidant atmosphere. The overall cost of the ultrathin copper foil is reduced, and meanwhile, the problem of oxidation of the ultrathin copper foil in the preparation process is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed circuit board processing, and in particular to a method for preparing an ultra-thin copper foil and a method for preparing a copper-clad plate using the ultra-thin copper foil. Background Art

[0002] With the rapid advancement and widespread application of 5G technology, the wiring accuracy and performance standards of integrated circuit packaging substrates continue to rise, posing a severe challenge to traditional etching processes, especially when realizing ultra-fine lines, it is difficult to take into account the dual optimization of etching factor and line width and line spacing. Against this background, m-SAP (modified semi-additive method) technology has emerged, which has completely revolutionized the process path of circuit manufacturing and greatly improved the accuracy and efficiency of manufacturing. The essence of m-SAP technology lies in the use of ultra-thin copper foil or copper-clad laminate covered with ultra-thin copper foil as the substrate. This innovative strategy perfectly combines the high-precision pattern transfer capability of photolithography technology with electroplating technology, making it possible to accurately construct circuits on a scale of 50 microns or even smaller, which perfectly meets the urgent needs of advanced packaging technology for high integration and miniaturization.

[0003] However, the physical and chemical properties of ultra-thin copper foil are accompanied by a series of challenges in production and application, such as easy curling, wrinkling, and easy oxidation, which undoubtedly increases the complexity of subsequent processing of ultra-thin copper foil. At present, the industry generally adopts the strippable carrier copper foil technology to prepare ultra-thin copper foil, and uses the chromic anhydride process to carry out anti-oxidation treatment on the surface of ultra-thin copper foil. The use of these processes has pushed up the production cost, environmental treatment cost and transportation cost of ultra-thin copper foil. Therefore, in the process of continuous evolution of packaging carrier technology, how to further optimize the production process of ultra-thin copper foil, reduce the overall cost of ultra-thin copper foil, and effectively prevent the oxidation problem of ultra-thin copper foil during the preparation process has become a technical problem and development direction that needs to be overcome urgently. Summary of the invention

[0004] The present invention provides a method for preparing an ultra-thin copper foil and a method for preparing a copper-clad laminate using the ultra-thin copper foil, so as to solve the above-mentioned deficiencies of the prior art, reduce the overall cost of the ultra-thin copper foil, and effectively prevent the oxidation problem of the ultra-thin copper foil during the preparation process.

[0005] In order to achieve the purpose of the present invention, the following technologies are proposed: On the one hand, a method for preparing an ultra-thin copper foil is provided, comprising the steps of: Step 01, soak the carrier substrate in a degreasing agent to remove oil stains on the surface; Step 02, preparing an organic active layer on the surface of the cleaned carrier substrate, wherein the thickness of the organic active layer is 1500-5000 Å, The organic active layer is prepared by coating the modified liquid A; Step 03, immersing the carrier substrate obtained after the treatment in step 02 into the modification liquid B, The soaking temperature is 20~30℃ and the soaking time is 30~70s; Step 04, placing the carrier substrate obtained after the treatment in step 03 into a copper electroplating solution for electroplating to prepare an ultra-thin copper foil, Current density is 1~20 A / dm 2 , the electrolyte temperature is 40-75°C, and the plating time is 10-80s; Step 05, washing and drying the ultra-thin copper foil obtained after the treatment in step 04; Step 06, performing an anti-oxidation treatment on the surface of the ultra-thin copper foil prepared in step 05 under a vacuum antioxidant atmosphere.

[0006] Furthermore, in step 01, the immersion time of the carrier substrate is 10-15 minutes, and the immersion temperature is 20-40°C.

[0007] Furthermore, in step 01, the material of the carrier substrate is polybenzimidazole, sulfonated polyimide, sulfonated polyaryletherketone, sulfonated polyarylether, or perfluorosulfonic acid polymer; Furthermore, in step 01, the thickness of the carrier substrate is 8-20 μm.

[0008] Furthermore, in step 01, the degreasing agent is a composition of nonylphenol polyoxyethylene ether or other non-ionic surfactant and deionized water, and the content of the non-ionic surfactant in the deionized water is 5-22wt%.

[0009] Further, in step 02, the solute of the modified solution A is one or a mixture of two of thiophene / pyrrole / furan / fluorene / condensed cyclic imide / indigo / isoindigo organic semiconductor polymers, and the molecular weight Mw of the solute of the modified solution A is ≤15 kDa; The solvent of the modified liquid A is a composition of deionized water and an organic solvent, and the volume ratio of water to the organic solvent is 1: (0.1-10); The organic solvent in the modified liquid A has a boiling point bp≤150°C and a toxicity LD50≥2900 mg / kg; And the total solute concentration of the modified solution A prepared by mixing is 1 to 15 g / L.

[0010] Further, the solute of the modified liquid B is one or two of the unsaturated ring small molecule (Mw≤200 g / mol) compounds of the thiazole / imidazole / pyridine / pyrimidine / triazole / piperazine type containing N / S elements and having a monoamino / thiol / sulfonate / carboxylate / sulfonic acid / carboxyl / hydroxyl group; The solvent of the modified liquid B is composed of deionized water and an organic solvent, and the volume ratio of water to the organic solvent is 1: (0.05~2); The boiling point of the organic solvent in the modified liquid B solvent is bp≤150℃, and the toxicity LD50 is ≥2900 mg / kg; The total solute concentration of the modified solution B is 1 to 5 g / L.

[0011] Further, the copper electroplating solution in step 04 has a copper salt concentration of 100 to 300 g / L; Sulfuric acid concentration is 50-120 g / L; Cl / Br ion concentration is 20~300 mg / L The concentration of sodium polydisulfide propane sulfonate is 0.2~1.2 g / L Hydroxymethylcellulose concentration ≤ 100 mg / L; Gelatin concentration ≤80 mg / L; Polyethyleneimine concentration ≤ 1000 mg / L; The molecular weight of polyethyleneimine is Mw≤10 kDa.

[0012] Furthermore, the antioxidant used in step 06 is composed of a small molecule of benzotriazole / benzimidazole / quinoxaline / benzothiazole / benzothiadiazole and a small molecule (Mw≤500 g / mol) of chlorinated / brominated alkane containing a monohydroxyl / carboxyl / thiol group. The molar ratio of antioxidant is 1:(0.8~1.2); The concentration of antioxidant atmosphere is 0.005~30 mL / L; The vacuum degree of antioxidant is Pv≤-0.1MPa; The operating temperature is 80~120℃; The antioxidant treatment time is 1~4 h.

[0013] On the other hand, a method for preparing a copper clad laminate is provided, wherein an ultra-thin copper foil 3 is prepared by a method for preparing an ultra-thin copper foil for a packaging carrier that can be stored for a long time, and is hot-pressed with a semi-cured sheet of epoxy resin / phenolic resin / polyester / polytetrafluoroethylene with a thickness of 1 to 30 mm at a hot-pressing temperature of 130 to 320 °C, a hot-pressing time of 2 to 6 h, and a hot-pressing pressure of 2 to 4.5 MPa.

[0014] The advantages of the above technical solution are: (1) Use a non-metallic peelable carrier substrate to replace the carrier copper foil to reduce the preparation cost of ultra-thin copper foil.

[0015] (2) There is moderate bonding force between the non-metallic peelable carrier substrate and the ultra-thin copper foil, which can ensure that the ultra-thin copper foil of the carrier composite film does not wrinkle or fall off during long-term storage and transportation.

[0016] (3) The ultra-thin copper foil can be completely and stably separated from the peelable carrier substrate after lamination, and the ultra-thin copper foil is difficult to peel off from the prepreg.

[0017] (4) The obtained ultra-thin copper foil with a peelable carrier substrate has good antioxidant ability and does not change color for 15 minutes at 140°C.

[0018] (5) The ultra-thin copper foil with a peelable carrier substrate can be stored for a long time, and the production of the ultra-thin copper foil with a peelable carrier substrate and the subsequent preparation of the copper clad laminate do not involve the use of highly toxic heavy metal cadmium (IV) salts, thus meeting environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0020] Figure 1 The figure shows the structure of the ultra-thin copper foil after preparation. DETAILED DESCRIPTION

[0021] like Figure 1 As shown, the structure of the finally prepared ultra-thin copper foil comprises a carrier substrate 1, an organic active layer 2 is coated on the upper side of the carrier substrate 1, an ultra-thin copper foil 3 is coated on the upper side of the organic active layer 2, and the carrier substrate 1 and the organic active layer 2 constitute a strippable carrier substrate. The existence of the strippable carrier substrate can avoid the ultra-thin copper foil 3 from wrinkling during storage, thereby solving the problem of inconvenient storage of the ultra-thin copper foil 3, and in order to facilitate the processing and production of copper-clad laminates, the ultra-thin copper foil 3 and the strippable carrier substrate are connected in a strippable manner, thereby facilitating the production of copper-clad laminates.

[0022] Example 1 Step 1: Using a 16 μm thick perfluorosulfonic acid membrane as a carrier substrate 1, soak it in a degreasing agent to remove surface stains. The perfluorosulfonic acid membrane soaking temperature is 30 ° C, and the soaking time is 10 min; the degreasing liquid is composed of OP-10 and deionized water, and the content of OP-10 in water is 15wt%.

[0023] Step 2: Prepare an organic active layer with a thickness of 2500 Å on the surface of the perfluorosulfonic acid membrane by electrospraying a modified liquid A. The modified liquid A used for electrospraying is composed of polyethylene dioxythiophene and a deionized water-ethanol mixed solvent (the content of ethanol in water is 10wt%), and the concentration of polyethylene dioxythiophene in the modified liquid A is 5 g / L.

[0024] Step 3, immerse the perfluorosulfonic acid membrane treated in the above step in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of 2-aminothiazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of 2-aminothiazole in modification solution A is 1 g / L.

[0025] Step 4, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L, sulfuric acid 75 g / L, Cl ion 70 mg / L, sodium polydisulfide bis(propylene sulfonate) 300 mg / L, polyethyleneimine (Mw = 0.2 kDa) 600 mg / L, hydroxymethyl cellulose 20 mg / L, and gelatin 20 mg / L.

[0026] The carrier substrate treated in the above steps is used as a cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water.

[0027] Step 5: Place the copper foil sample obtained in the above step in a vacuum drying oven (vacuum degree -0.1MPa) and perform antioxidant treatment in an antioxidant atmosphere at a treatment temperature of 100°C for a treatment time of 2 hours. The antioxidant is a mixture of benzotriazole and 1-chloro-6-mercaptohexane (the molar ratio of benzotriazole to 1-chloro-6-mercaptohexane is 1:0.8), and the concentration of the antioxidant in the oven is 5mL / L.

[0028] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in the above step is hot-pressed with a FR4 epoxy resin substrate with a thickness of 12 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 200°C, a hot-pressing time of 3 h, and a hot-pressing pressure of 4 MPa.

[0029] Example 2 Step 1: Using a 16 μm thick perfluorosulfonic acid membrane as a carrier substrate 1, soak it in a degreasing agent to remove surface stains. The perfluorosulfonic acid membrane soaking temperature is 30 ° C, and the soaking time is 10 min; the degreasing liquid is composed of OP-10 and deionized water, and the content of OP-10 in water is 15wt%.

[0030] Step 2: Prepare an organic active layer with a thickness of 2500 Å on the surface of the perfluorosulfonic acid film by electrospraying a modified liquid A. The modified liquid A used for electrospraying is composed of polypyrrole-block-polycaprolactone and a deionized water-ethanol mixed solvent (the content of ethanol in water is 10wt%), and the concentration of polypyrrole-block-polycaprolactone in the modified liquid A is 8 g / L.

[0031] Step 3, immerse the perfluorosulfonic acid membrane treated in the above step in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of 2-aminothiazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of 2-aminothiazole in modification solution A is 1 g / L.

[0032] Step 4, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L, sulfuric acid 75 g / L, Cl ion 70 mg / L, sodium polydisulfide bis(propylene sulfonate) 300 mg / L, polyethyleneimine (Mw = 0.2 kDa) 600 mg / L, hydroxymethyl cellulose 20 mg / L, and gelatin 20 mg / L.

[0033] The carrier substrate treated in the above steps is used as a cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water.

[0034] Step 5: Place the copper foil sample obtained in the above step in a vacuum drying oven (vacuum degree -0.1MPa) and perform antioxidant treatment in an antioxidant atmosphere at a treatment temperature of 100°C for a treatment time of 2 hours. The antioxidant is a mixture of 2-mercaptobenzothiazole and 1-chloro-6-carboxyhexane (the molar ratio of 2-mercaptobenzothiazole to 1-chloro-6-carboxyhexane is 1:0.8), and the concentration of the antioxidant in the oven is 5mL / L.

[0035] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in the above step is hot-pressed with a FR4 epoxy resin substrate with a thickness of 12 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 200°C, a hot-pressing time of 3 h, and a hot-pressing pressure of 4 MPa.

[0036] Example 3 Step 1: Using a 16 μm thick perfluorosulfonic acid membrane as a carrier substrate 1, soak it in a degreasing agent to remove surface stains. The perfluorosulfonic acid membrane soaking temperature is 30 ° C, and the soaking time is 10 min; the degreasing liquid is composed of OP-10 and deionized water, and the content of OP-10 in water is 15wt%.

[0037] Step 2: Prepare an organic active layer with a thickness of 2500 Å on the surface of the perfluorosulfonic acid membrane by electrospraying a modified liquid A. The modified liquid A used for electrospraying is composed of poly(3-octylthiophene-2,5-diyl) and a deionized water-ethanol mixed solvent (the content of ethanol in water is 10 wt%), and the concentration of poly(3-octylthiophene-2,5-diyl) in the modified liquid A is 6 g / L.

[0038] Step 3, immerse the perfluorosulfonic acid membrane treated in the above step in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of 2-aminothiazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of 2-aminothiazole in modification solution A is 1 g / L.

[0039] Step 4, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L, sulfuric acid 75 g / L, Cl ion 70 mg / L, sodium polydisulfide bis(propylene sulfonate) 300 mg / L, polyethyleneimine (Mw = 0.2 kDa) 600 mg / L, hydroxymethyl cellulose 20 mg / L, and gelatin 20 mg / L.

[0040] The carrier substrate treated in the above steps is used as a cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water.

[0041] Step 5: Place the copper foil sample obtained in the above step in a vacuum drying oven (vacuum degree -0.1MPa) and perform antioxidant treatment in an antioxidant atmosphere at a treatment temperature of 100°C for a treatment time of 2 hours. The antioxidant is a mixture of 2,1,3-benzothiadiazole and 1-chloro-6-hydroxyhexane (the molar ratio of 2,1,3-benzothiadiazole to 1-chloro-6-hydroxyhexane is 1:0.8), and the concentration of the antioxidant in the oven is 5mL / L.

[0042] Step 6, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in the above step is hot-pressed with a FR4 epoxy resin substrate with a thickness of 12 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 200°C, a hot-pressing time of 3 h, and a hot-pressing pressure of 4 MPa.

[0043] Reference example Step 1: Using a 16 μm thick perfluorosulfonic acid membrane as a carrier substrate 1, soak it in a degreasing agent to remove surface stains. The perfluorosulfonic acid membrane soaking temperature is 30 ° C, and the soaking time is 10 min; the degreasing liquid is composed of OP-10 and deionized water, and the content of OP-10 in water is 15wt%.

[0044] Step 2: Prepare an organic active layer with a thickness of 2500 Å on the surface of the perfluorosulfonic acid membrane by electrospraying a modified liquid A. The modified liquid A used for electrospraying is composed of polyethylene dioxythiophene and a deionized water-ethanol mixed solvent (the content of ethanol in water is 10wt%), and the concentration of polyethylene dioxythiophene in the modified liquid A is 5 g / L.

[0045] Step 3, immerse the perfluorosulfonic acid membrane treated in the above step in modification solution B, the immersion temperature is 30 ° C, and the immersion time is 60 s. Modification solution B is composed of 2-aminothiazole and deionized water-isopropanol mixed solvent (isopropanol content in water is 10wt%); the concentration of 2-aminothiazole in modification solution A is 1 g / L.

[0046] Step 4, prepare a copper electroplating solution. The copper electroplating solution consists of the following components: Copper sulfate pentahydrate 200 g / L, sulfuric acid 75 g / L, Cl ion 70 mg / L, sodium polydisulfide bis(propylene sulfonate) 300 mg / L, polyethyleneimine (Mw = 0.2 kDa) 600 mg / L, hydroxymethyl cellulose 20 mg / L, and gelatin 20 mg / L.

[0047] The carrier substrate treated in the above steps is used as a cathode and immersed in a 60 ℃ copper electroplating solution for segmented electroplating. DC electroplating is first performed with a current density of 20 A / dm 2 , electroplating time 20 s, then square wave / triangle wave pulse electroplating, current density range 40 A / dm 2 , the pulse on time range is 100 ms, and the pulse off time range is 20-1500 ms. After the electroplating is completed, take it out and rinse it with deionized water.

[0048] Step 5, according to the required thickness and shape of the final copper clad laminate, the ultra-thin copper foil obtained in the above step is hot-pressed with a FR4 epoxy resin substrate with a thickness of 12 mm, and cooled to obtain the required copper clad laminate, with a hot-pressing temperature of 200°C, a hot-pressing time of 3 h, and a hot-pressing pressure of 4 MPa.

[0049] Table 1 Performance test results Note: The peel strength in the table is tested according to the IPC-TM-650 test standard.

[0050] According to the results in Table 1, the ultra-thin copper foil obtained based on Examples 1 to 3 has good anti-oxidation properties and can be completely peeled off from the carrier substrate during the copper clad laminate lamination process. After lamination, there is good bonding strength between the copper foil and the prepreg. In addition, the ultra-thin copper foil obtained can be stored for a long time.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an ultra-thin copper foil, characterized in that: Includes steps: Step 01, soaking the carrier substrate (1) with a degreasing agent; Step 02, preparing an organic active layer (2) on the surface of the carrier substrate (1), wherein the thickness of the organic active layer (2) is 1500-5000 Å; The organic active layer (2) is prepared by coating the modified liquid A; Step 03, immersing the carrier substrate (1) obtained after the treatment in step 02 into the modification liquid B, The soaking temperature is 20~30℃ and the soaking time is 30~70s; Step 04, placing the carrier substrate (1) obtained after the treatment in step 03 into a copper electroplating solution to prepare an ultra-thin copper foil (3) by electroplating. Current density is 1~20 A / dm 2 , the electrolyte temperature is 40-75°C, and the plating time is 10-80s; Step 05, washing and drying the ultra-thin copper foil (3) obtained after the treatment in step 04; Step 06, performing an anti-oxidation treatment on the surface of the ultra-thin copper foil (3) prepared in step 05 in a vacuum antioxidant atmosphere.

2. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: In step 01, the carrier substrate (1) is immersed for 10 to 15 minutes at a temperature of 20 to 40°C.

3. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: In step 01, the material of the carrier substrate (1) is polybenzimidazole, sulfonated polyimide, sulfonated polyaryletherketone, sulfonated polyarylether, or perfluorosulfonic acid polymer.

4. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: In step 01, the thickness of the carrier substrate (1) is 8-20 μm.

5. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: In step 01, the degreasing agent is a composition of nonylphenol polyoxyethylene ether or other non-ionic surfactant and deionized water, and the content of the non-ionic surfactant in the deionized water is 5-22wt%.

6. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: In step 02, the solute of the modified solution A is one or a mixture of two of thiophene / pyrrole / furan / fluorene / condensed cyclic imide / indigo / isoindigo organic semiconductor polymers, and the molecular weight Mw of the solute of the modified solution A is ≤15 kDa; The solvent of the modified liquid A is a composition of deionized water and an organic solvent, and the volume ratio of water to the organic solvent is 1: (0.1-10); The organic solvent in the modified liquid A has a boiling point bp≤150°C and a toxicity LD50≥2900 mg / kg; And the total solute concentration of the modified solution A prepared by mixing is 1 to 15 g / L.

7. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: The solute of modified liquid B is one or two of the unsaturated ring small molecule (Mw≤200 g / mol) compounds of monoamino / thiol / sulfonate / carboxylate / sulfonic acid / carboxyl / hydroxyl groups of thiazole / imidazole / pyridine / pyrimidine / triazole / piperazine containing N / S elements; The solvent of the modified liquid B is composed of deionized water and an organic solvent, and the volume ratio of water to the organic solvent is 1: (0.05~2); The boiling point of the organic solvent in the modified liquid B solvent is bp≤150℃, and the toxicity LD50 is ≥2900 mg / kg; The total solute concentration of the modified solution B is 1 to 5 g / L.

8. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: The copper electroplating solution in step 04 has a copper salt concentration of 100 to 300 g / L; Sulfuric acid concentration is 50-120 g / L; Cl / Br ion concentration is 20~300 mg / L The concentration of sodium polydisulfide propane sulfonate is 0.2~1.2 g / L Hydroxymethylcellulose concentration ≤ 100 mg / L; Gelatin concentration ≤80 mg / L; Polyethyleneimine concentration ≤ 1000 mg / L; The molecular weight of polyethyleneimine is Mw≤10 kDa.

9. The method for preparing the ultra-thin copper foil according to claim 1, characterized in that: The antioxidant used in step 06 is composed of benzotriazole / benzimidazole / quinoxaline / benzothiazole / benzothiadiazole small molecules and small molecules (Mw≤500 g / mol) containing monohydroxyl, carboxyl, and thiol groups and chlorinated / brominated alkanes. The molar ratio of antioxidant is 1:(0.8~1.2); The concentration of antioxidant atmosphere is 0.005~30 mL / L; The vacuum degree of antioxidant is Pv≤-0.1MPa; The operating temperature is 80~120℃; The antioxidant treatment time is 1~4 h.

10. A method for preparing a copper clad laminate, characterized in that: The ultra-thin copper foil (3) is prepared by the method for preparing the ultra-thin copper foil according to any one of claims 1 to 9, and is hot pressed with a semi-cured sheet of epoxy resin, phenolic resin, polyester, or polytetrafluoroethylene with a thickness of 1 to 30 mm at a hot pressing temperature of 130 to 320 °C, a hot pressing time of 2 to 6 h, and a hot pressing pressure of 2 to 4.5 MPa.